2013
DOI: 10.1111/are.12324
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E requirement of sea cucumber (Apostichopus japonicus) and its' effects on nonspecific immune responses

Abstract: This feeding trial was conducted to determine the vitamin E requirement of sea cucumber (Apostichopus japonicus) and to study the effects of vitamin E on nonspecific immune parameters. Commercial sea cucumber diets supplemented with 0, 50, 100, 200, 500 or 1000 mg kg À1 vitamin E were fed to juvenile sea cucumber (7.96 AE 0.01 g) for 60 days. Specific growth rate and total coelomocyte counts were maximized in sea cucumber fed diets supplemented with 100 mg kg À1 vitamin E. Reactive oxygen species production wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 38 publications
2
10
2
Order By: Relevance
“…Furthermore, Peng et al () observed that oxidized oil fed black sea bream improved the growth performance and liver α‐tocopherol content after feeding with vitamin E (150 mg/kg) supplemented diet. Similarly, increase in α‐tocopherol level in tissues and reduction in lipid peroxidation of oxidized oil ingested fish by dietary supplementation of vitamin E have been reported by Huang and Huang () in tilapia, Chen, Li, Yu, Du, and Chen () in largemouth bass, Zhong et al () in Atlantic cod, Wang et al () in crab and Wang et al () in large yellow croaker. Nevertheless, no report is available on carps, which are farmed majorly in Eurasia.…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…Furthermore, Peng et al () observed that oxidized oil fed black sea bream improved the growth performance and liver α‐tocopherol content after feeding with vitamin E (150 mg/kg) supplemented diet. Similarly, increase in α‐tocopherol level in tissues and reduction in lipid peroxidation of oxidized oil ingested fish by dietary supplementation of vitamin E have been reported by Huang and Huang () in tilapia, Chen, Li, Yu, Du, and Chen () in largemouth bass, Zhong et al () in Atlantic cod, Wang et al () in crab and Wang et al () in large yellow croaker. Nevertheless, no report is available on carps, which are farmed majorly in Eurasia.…”
Section: Introductionsupporting
confidence: 58%
“…Furthermore, in our study, higher deposition of α‐tocopherol was observed in fish fed fresh oil compared to fish which was fed oxidized oil. Lower detection of α‐tocopherol content in such fish groups indicates its higher utilization in alleviating the oxidative stress caused by oxidized dietary oil (Wang et al, ). This effect was more prominent in the liver tissues as compared to muscle tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four isonitrogenous and isolipidic diets (20.4% crude protein and 3.65% crude lipid) (Seo and Lee, 2011) were formulated: a control diet containing 50% Sargassum thunbergii, and 3 treatment diets in which 20% (R20), 40% (R40) and 60% (R60) proteins from S. thunbergii was substituted with the proteins from the mixture of corn kernels meal and soybean meal. Shell powder was used to regulate the main nutritional composition such as the protein and lipid in different diets to formulate the isoproteic and isolipidic diets, and it was also used as the calcium source in formulated diets (Xia et al, 2013;Wang et al, 2015).…”
Section: Experimental Dietsmentioning
confidence: 99%
“…Successful culture of sea cucumber requires both knowledge of nutrient requirements and suitable feeds. Thus numerous studies have focused on the nutrient requirements (Okorie et al, 2008;Seo and Lee, 2011;Wang et al, 2015) and optimal feed ingredients (Liu et al, 2010;Gao et al, 2011;Seo et al, 2011a, Xia et al, 2012 for this species.…”
Section: Introductionmentioning
confidence: 99%